Circuit modeling for UWB-MIMO antenna array - Kasi B.; Jalil Y.E.; Chakrabarty C.K. (IEEE Computer Society, 2023)
In this article a simple analytical model for a UWB-MIMO antenna is proposed. Lumped equivalent circuit elements are used to construct the proposed MIMO array. Parameters of the circuit elements are calculated from the geometry of the designed antenna. Using frequency transformation technique causes the antenna to have wider impedance bandwidth and compact size. Mutual coupling effect is also taken into consideration for better circuit modeling. The proposed model has been developed using simulations and measurements based techniques. The calculated data are compared with the experimental results and good agreement is noted. 2013 IEEE.